Refractive Errors in Children with Retinoblastoma - S. V. Saakyan; A. Iu. Tsygankov; S. S. Tadevosyan; A. A. Makarova; L. V. Kogoleva; R. A. Tatskov (Oftalʹmologiâ)
Purpose. Analysis of refractive errors’ frequency in children with retinoblastoma.Patients and Methods. A retrospective study included 57 children with retinoblastoma (31 male and 26 female) who received treatment in 2013–2017. The criteria for patient selection was the presence of mono- or bilateral retinoblastoma, as well as autorefractometry of both eyes before treatment. In all cases, the study was performed with cycloplegia. The parameters studied included gender, age at the time of the initial examination, visual acuity, spherical and cylindrical component of refraction, the axis of the cylinder.Results. Bilateral retinoblastoma was determined in 34 children (59.6 %), the average age of the patients was 18.0 ± 2.6 months. Monolateral retinoblastoma was detected in 23 patients (40.4 %), the average age at the time of check-up was 26.2 ± 3.1 months. In total, anisometropia of more than 2.0 diopters was detected in 14 patients (24.6 %), of which with monolateral RB in 6 patients (26.1 %) and in bilateral patients in 8 (23.5 %). In 26 cases (45.6 %) anisometropia was determined from 1.0 to 2.0 diopters, of which 41.1 % (n = 14) with bilateral lesion and 52.1 % (n = 12) with monolateral. The frequency of hyperopia over 3.0 diopters in the total cohort was 25.2 %, myopia 3.3 %. Significant differences (p = 0.025) were obtained by comparing the frequency of astigmatism determination of more than 1.0 D (39.6 % in the total cohort versus 13.0 % for healthy eyes). When analyzing the frequency of ametropia depending on age, a trend was observed (0.05 < p < 0.1) to reduce the frequency of hypermetropia and increase the frequency of astigmatism. Additionally, an analysis of the astigmatism’s frequency depending on the tumor localization was made. Patients with central or paracentral localization of the tumor lesion amounted to 69.4 % (n = 25), and from the peripheral — 30.6 % (n = 11) (p = 0.002).Conclusions. In this paper, we analyzed the frequency and nature of refractive errors in children with monolateral and bilateral retinoblastoma. The identified risk factors may affect the development of refractive amblyopia in children with retinoblastoma in more adulthood, which requires the development of an individual approach to the correction of refractive disorders taking into account the localization of tumor foci, the nature of the lesion and the individual characteristics of patients.